Children Living with HIV: A Narrative review of Recent Advances in Paediatric HIV Research and their Implications for Clinical Practice - Nalwanga, Damalie; Musiime, Victor (Therapeutic Advances in Infectious Disease, 2022)
Despite the great strides that have been made in prevention of mother to child transmission (PMTCT), children continue to acquire HIV. The reduction in transmission is variable, for example in Africa, great gains have been made in Eastern and Southern Africa, but critical gaps remain in West and Central Africa. These gaps are also observed in the treatment of children living with HIV. Although there is increased access to lifesaving antiretroviral therapy (ART), management of pediatric HIV infection continues to be a challenge to clinicians in low-income countries where the disease burden is disproportionately high. On the contrary, recent advances in ART drug types and formulations provide great hope. In this narrative review, we present key updates in HIV care and promising ART research among children and adolescents living with HIV. We particularly highlight the dolutegravir (DTG) research which informed the change of the World Health Organization (WHO) ART guidelines in this age group. Significant gaps remain around management of children presenting with advanced disease to minimize mortality and in the long-term care and treatment of adolescents living with HIV. Research to address these sensitive areas is crucial for the realization of global, regional, and national pediatric HIV targets.
Keywords: HIV; Pediatric; Children